Transhumanism Ethics: A Critical Analysis of AI Technology Development and Its Implications for Humanity - Huda, Achmad Nuril; Winarno, Agung; Yahya, Khoirul (Journal of Islamic Thought and Philosophy, 2024)
This study examines the ethics of transhumanism in the development of artificial intelligence (AI) technology and its implications for humanity through the perspective of Immanuel Kant’s deontological ethics. The research focuses on the threats to human dignity, moral autonomy, and social injustice arising from the application of transhumanism. Using a qualitative research method based on a literature review, the findings reveal that AI development within the framework of transhumanism tends to violate universal moral principles by treating humans as mere instruments for technological progress. Additionally, autonomous AI has the potential to eliminate human moral responsibility, increase dependency on technology, and deepen the inequality of access between affluent and underprivileged groups. This study recommends AI development policies that emphasize respect for human dignity, moral autonomy, and equitable technology distribution to prevent the risks of dehumanization and social inequality.